Inhibition of Rumen Methanogens by a Novel Archaeal Lytic Enzyme Displayed on Tailored Bionanoparticles - Altermann, Eric; Schofield, Linley R.; Ronimus, Ron S.; Beattie, Amy K.; Reilly, Kerri (Frontiers in Microbiology, 2018)
Methane is a potent greenhouse gas, twenty-five times more efficient at trapping heat than carbon dioxide. Ruminant methane emissions contribute almost 30% to anthropogenic sources of global atmospheric methane levels and a reduction in methane emissions would significantly contribute to slowing global temperature rises. Here we demonstrate the use of a lytic enyzme, PeiR, from a methanogen virus that infects Methanobrevibacter ruminantium M1 as an effective agent inhibiting a range of rumen methanogen strains in pure culture. We determined the substrate specificity of soluble PeiR and demonstrated that the enzyme is capable of hydrolysing the pseudomurein cell walls of methanogens. Subsequently, peiR was fused to the polyhydroxyalkanoate (PHA) synthase gene phaC and displayed on the surface of PHA bionanoparticles (BNPs) expressed in Eschericia coli via one-step biosynthesis. These tailored BNPs were capable of lysing not only the original methanogen host strain, but a wide range of other rumen methanogen strains in vitro. Methane production was reduced by up to 97% for 5 days post-inoculation in the in vitro assay. We propose that tailored BNPs carrying anti-methanogen enzymes represent a new class of methane inhibitors. Tailored BNPs can be rapidly developed and may be able to modulate the methanogen community in vivo with the aim to lower ruminant methane emissions without impacting animal productivity.